👤

B = (x + 4) (2x + 4)
D = (5x + 4) (2x + 7)
Aidez moi svpp


Répondre :

B = (x + 4) (2x + 4)

   = x*2x + x*4 + 4*2x + 4*4

   = 2x²   + 4x   + 8x   + 16

   = 2x² + 12x + 16

et

D = (5x + 4) (2x + 7)

   = 5x*2x + 5x*7 + 4*2x + 4*7

   = 10x² + 35x + 8x + 28

   = 10x² + 43x + 28

avec * = multiplié par

puisque (a+b) (c+d) = ac+ad+bc+bd

Bonsoir,

Développer puis réduire :

B = (x + 4)(2x + 4)

B = x × 2x + 4x + 4 × 2x + 4 × 4

B = 2x² + 12x + 16

D = (5x + 4)(2x + 7)

D = 5x × 2x + 5x × 7 + 4 × 2x + 4 × 7

D = 10x² + 43x + 28

Bonne soirée.